Մշոյ Ս. Առաքելոց, Մատնավանք և Ս. Յովհաննէս վանքերու թեմական գիւղերու, Բասենի ու Թախթի հայկական եկեղեցիներու, վանքերու և գերեզմանատուներու անտիպ ցուցակ (1861-1866 թթ.) - Մինասեան, Միհրան (Մատենադարան)
The article presents a previously unpublished document of historical value which contains lists, compiled in 1861–1866, of Armenian-populated villages, functioning and abandoned monasteries, churches and cemeteries in several districts geographically far from each other. The first part contains a list of 54 diocesan villages of the Arakelots Monastery (Surp Ghazaros, Tarkmanchats), with the numbers of Armenian houses in each village. Then a list of 8 diocesan villages of the Madnavank Monastery is given, which also contains the numbers of houses. It is followed by a list of 67 diocesan villages of the monastery of Surp Hovhannes (Yeghertud), the third of the historical monasteries of Mush. 10 villages in the list also contain the numbers of houses. Thus, in total, the document presents 129 Armenian-populated villages, 72 of which contain the numbers of Armenian houses. This is followed by a list of existing and abandoned monasteries and churches of the Pasen district. It contains information about 6 monasteries, 8 churches and more than 10 cemeteries located in 13 villages. The last part of the document is entitled “Churches and cemeteries discovered in the Turkish villages of the Takht diocese.” It contains information about 22 Armenian churches, 29 cemeteries and 1 fortress. These were found in 36 Turkish villages of the Takht district of the Gars region. Important news for a researcher in the published document is the information about the number of Armenian houses in the Mush Valley and its environs – this is one of the first attempts of collecting statistical data. The lists of churches and cemeteries in the villages abandoned by the Armenians are also important, especially since there is no evidence on many of them in other sources. The lists confirm that those villages were Armenian. В статье представлен ранее не публиковавшийся документ, представляющий историческую ценность. Он содержит составленные в 1861-1866 годах списки сёл, населенных армянами, действующих и покинутых монастырей, церквей и кладбищ в нескольких друг от друга округах. В первой части приводится список 54 епархиальных сёл монастыря Аракелоц (св. Газарос, Таргманчац), с числом армянских домов в каждом селе, затем даётся список 8 епархиальных сёл монастыря Матнаванк, в котором также содержатся данные о числе домов. В завершение приводится список 67 епархиальных сёл монастыря Сурб Ованес (Егрдут), третьего из монастырей Муша; 10 сёл из списка содержат данные о численности домов. Таким образом, суммарно в документе представлены данные о 129 сёлах, населенных армянами; из них по поводу 72 сел приводятся данные о численности армянских домов. Затем следует список действующих и покинутых монастырей и церквей округа Басен, который содержит сведения о 6-и монастырях, 8-и церквях и более чем 10-и кладбищах, находящихся в 13-и деревнях. Последняя часть документа озаглавлена «Церкви и кладбища, обнаруженные в заселенных турками селениях Тахтской епархии», которая содержит сведения о 22-х армянских церквях, 29-и кладбищах и одной крепости, обнаруженных в 36-и турецких деревнях округа Тахт Карской области. Важной новостью в публикуемом документе является содержащиеся в нем сведения о числе армянских домов Мушской долины и его окрестностей-это одна из первых попыток сбора статистических данных. Важны также списки церквей и кладбищ в покинутых армянами сёлах, которые подтверждают армянскую принадлежность этих сёл, тем более, что данные о многих из них в других источниках отсутствуют.
Keywords: Հայկական եկեղեցիներ